2013
DOI: 10.2967/jnumed.113.127266
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Cerenkov Luminescence Imaging of18F-FDG

Abstract: The aim of this study was to determine the feasibility of Cerenkov luminescence (CL) imaging of patients undergoing diagnostic 18F-FDG scans to detect nodal disease. Methods Patients undergoing routine 18F-FDG PET/CT for various malignancies consented to being scanned for CL. White-light and Cerenkov images (5-min acquisition) of the surface of the patient contralateral to and at the site of nodal 18F-FDG uptake were acquired using a cooled, intensified charge-coupled-device camera. Results The camera demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 15 publications
2
150
0
1
Order By: Relevance
“…Like other optical imaging techniques, tissue penetrating limitation and low sensitivity for deep targets are the intrinsic limitations of CLI 25,32 . 39,40 . Compared to PET imaging, CLI can be performed with a relatively low cost imaging system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other optical imaging techniques, tissue penetrating limitation and low sensitivity for deep targets are the intrinsic limitations of CLI 25,32 . 39,40 . Compared to PET imaging, CLI can be performed with a relatively low cost imaging system.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to PET imaging, CLI can be performed with a relatively low cost imaging system. Recently, Thorek et al demonstrated that significantly high sensitivity could be achieved with CLI as low amounts of 18 F-FDG accumulated (about 2Ci) in the nodes of patients 39,40 . In vitro testing indicated that CLI signal from 0.01 Ci 90Y was detectable in solution 25,32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CL of isotopes traditionally used for PET imaging is poor, and the re-use of established PET tracers for CLI is therefore limited. Although frequencies produced in pure CL are heavily attenuated, limiting penetration depth and sensitivity 79,[81][82][83] , it is possible to shift the effective frequency of CLI-probe emission toward the NIR through the incorporation of fluorophores into CLI probes. Herein, characteristic ultraviolet-blue CR is absorbed by a fluorophore and re-emitted at lower NIR-visible frequencies, enhancing tissue penetration and facilitating detection, and therefore increasing the utility of CL in the clinic.…”
Section: Pet/spect-oimentioning
confidence: 99%
“…Since Cerenkov imaging uses light emission caused by β-particles travelling through a medium, detection of these signals seems to be the most straightforward technique to include an optical imaging readout in a nuclear medicine setting. This technique can be applied to known PET tracers such as 18 F-FDG [6]. While the low photon flux (amount of emitted light) and the unfavourable wavelength (the peak of the emitted light lies in the wavelength area with maximal tissue absorbance, <400 nm) are major limiting factors, the technique has nevertheless already been successfully applied in both preclinical and clinical settings.…”
Section: Optical Imaging As An Add-on To Nuclear Imagingmentioning
confidence: 99%